Redução na expressão da proteína G3BP1 de grânulos de estresse sensibiliza células de glioblastoma tratadas com quimioterápicos - Lucas Felipe Fernandes Bittencourt (2019)
Glioblastoma multiforme (GBM) is the most lethal form of gliomas. These astrocytic-derived pathologies have been studied for many years, yet, not actual cure was achieved with regular treatments. New therapies are currently in development to tackle treatment limitations. In this work, we aim to inhibit a stress-related cellular response triggered by chemotherapeutic agents. Thus, non-membranal organelles known as Stress Granules (SGs) allow cells to recruit and protect vital mRNAs during stress and, when conditions improve, release these mRNAs to resume cells normal activities. This SGs are composed of various proteins, being G3BP1, a core element that enucleates and therefore, results in SGs assembly. Interfering in G3BP1 mRNA and protein expression with short-interference RNA, we were able to successfully diminish SGs assembly. Using calculated IC50 of three chemotherapeutic agents (Bortezomib – proteasome inhibitor, Etoposide – Topoisomerase II inhibitor and Temozolomide – alkylating agent) we observed a reduced cell viability with MTT assay when comparing negative controls and G3BP1 knocked down cells. To elucidate how cells were losing viability in a G3BP1-dependent manner we performed the apoptotic hallmark assay Annexin V/7-AAD concerning phosphatidyl serine domains exposition (PS) and necrosis. Negative control BZM treated group displayed no increased apoptosis when comparing to control without drugs, however, G3BP1 silenced BZM group had a significative increased in apoptotic response. Through Caspase 3 protein quantification by immunoblotting confirmed BZM G3BP1 silenced effects, increasing protein quantity when compared to negative BZM treated group and control groups. In order to better comprehend cells viability loss, we performed a lysosomal accumulation assay which revealed increased autophagy in U87 cells treated with TMZ when SGs were impaired. Further on, we assayed a late stage autophagy assay with acridine orange in a time-course regimen, as results we obtained increased acidic vesicles at 8H for U87 treated with ETO and TMZ and 10-12H for T98 treated with BZM/ETO and TMZ, respectively. Based onobtained results we assesses cells LC3B expression, an early autophagic assay, in time-point prior to ones obtained with AO. Our results demonstrated a possible increase in LC3B expression in U87 cells treated TMZ for 6H and in T98 cells treated with ETO and TMZ for 8 hours. In parallel, we observed a reduced VEGF-independent angiogenesis in SG impaired U87 cells treated with BZM. We can conclude that autophagy probably has a pivotal role in reducing cellular viability in SG impaired U87 TMZ-treated cells All data obtained leads to a new and exciting phenomenon of apoptotic potentializing, anti-angiogenic effects in U87MG GBM cells with impaired SGs assembly.